The leverage of brand image and perceived quality towards purchasing decisions mediating role of consumer satisfaction - Rafli, Muhammad; Mangruwa, Rajiv (Institute of Computer Science (IOCS), 2023)
The lifestyle has unique influence in the fashion. Indonesian fashion is continuously changing over the trends. There is an influx of fashion enterprises into Indonesia. Consumer purchases are one aspect of a business's success. Brand image, perceived quality, and customer satisfaction are just a few of the numerous variables that might have an impact on a purchase decision. The aim of this research is to determine how much brand image and perceived quality influences purchasing decisions through customer satisfaction. This study used a quantitative approach. Using purposive sampling, 150 samples total were employed in this investigation. Data analysis was used with the software Smart-PLS SEM. The study's found that purchase decisions are significantly influenced by brand image. Customer satisfaction is not much impacted by brand image. Decisions on what to buy are not much influenced by perceived quality. Customer happiness is significantly impacted by perceived quality. Decisions about what to buy are greatly influenced by customer happiness. Consumer happiness has no discernible impact on brand image in terms of purchasing decisions. The study recommends to increases customer happiness, perceived quality has a big impact on buying decisions